79GHz Substrate Integrated Waveguide antenna for short-range radar applications. Issue 1 (May 2021) - Santhakumar, G; Vadivelu, R; Revathy Lakshmi, M; Saranya, G J; Subasini, R
Abstract: It is evident that radar sensing is robust technology compared to camera or LiDAR in the case of autonomous vehicles. Since, they are capable of working even under harsh weather conditions like thick fog, glaring sun, etc. The 77-81GHz frequency band for short range radar provides a global framework for automotive radar by preventing collisions, reducing traffic accidents and thus improvingvehicular safety. The proposed antenna resonates at 79GHz. Below-10dB, return loss characteristic greater than -35dB is obtained in the band of 77.5GHz to 80.4GHz (i.e., impedance bandwidth of 2.86GHz) and gain of above 8dB is achieved. Rectangular vias and complementary concentric square loops of the metamaterial structure are introduced to suppress the surface waves and to achieve the desired frequency of resonance. The feed line and the metamaterial structure are positionedaccordinglyto provide a better impedance matching. VSWR obtained is 1.04 and the antenna is linearly polarized and has a low profile. The total dimension of the antenna is 1.96×2.26×0.127mm 3 . The antenna structure can be used in an array for automotive radar applications.